Draft Genome Sequence of Mycobacterium tuberculosis KT-0192, Isolated in South Korea - Lee, Sanghyun (Genome Announc, 2016)
We report the draft genome sequence of totally drug-resistant (XDR) Mycobacterium tuberculosis KT-0192. This sequence will provide new insights into the main cause and evolution of drug resistance in M. tuberculosis KT-0192.